TECHNIQUES FOR THE DEVELOPMENT OF SPEECH OF YOUNG LEARNERS - Tashpulatova FotimaUngarovna, Sharipova MakhmudaZoitovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The present work is devoted to characterizing the methodology for the development of speech of young learners when working on phrases and sentences. The purpose of the work is to show how the work on phrases and sentences in the English lessons, in general, affects the development of speech of younger students.